Pengaruh Hipnoterapi Lima Jari terhadap Kecemasan pada Lansia di Ruang Rawat Inap Paviliun Kusuma Rumah Sakit Pusri Palembang: Penelitian - Euis Permata Sari; Riko Sandra Putra (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Anxiety in hospitalized elderly patients can negatively impact their psychological and physical well-being. This study aims to determine the effect of Five-Finger Hypnotherapy on anxiety in elderly patients in the Inpatient Pavilion Kusuma, Pusri Hospital, Palembang. This study employed a quasi-experimental design using a pretest-posttest one-group design. The sample consisted of 18 elderly patients selected through purposive sampling. The research instrument used was the Hamilton Anxiety Rating Scale (HARS), and data analysis was conducted using the paired sample test. The results indicated a significant effect of Five-Finger Hypnotherapy on reducing anxiety in elderly patients in the Inpatient Pavilion Kusuma, Pusri Hospital, Palembang, with a significance value of 0.000 (p < 0.05). Based on these findings, Five-Finger Hypnotherapy is recommended as a non-pharmacological intervention to reduce anxiety in elderly patients in hospital settings.